FEMALE STUDENTS PERCEIVED CAUSES OF AND SOLUTION TO EXAMINATION MALPRACTICE IN ASA LOCAL GOVERNMENT: IMPLICATION FOR COUNSELLING - Oniye, Abdulrazaq Olayinka; Alawaye, Aminullahi Salman (Sokoto Educational Review, 2020)
Examination malpractice is rated as one of the greatest problems that undermine the foundation of educational practice in Nigeria today. The magnitude of the problem and the dangers posed by the phenomenon have been identified by stakeholders as national malady that require drastic solution. Thus, this study attempted to investigate the view of female students about the causes o f and solutions to examination malpractices. A total of five hundred female students were sampled from ten selected schools in Asa Local Government Area of Kwara State for the study. Data were collected with the use of researcher developed questionnaire. Two (2) research questions were raised and answered using frequency counts, simple percentage and means scores. Three (3) hypotheses raised for the study were tested at 0.05 alpha level. However, results indicated that societal preference for paper qualification; inadequate preparation for examination, lack of self-confidence, ill equipped schools, lack of good study habits and host of others were considered by female students as the causes of examination malpractice. The identified solutions range from restoring discipline in every facet of our national life, strict and thorough invigilation, employment of function counsellors in schools etc. Based on these findings, it was recommended that the government should sensitizes all citizens to basic ethical values of self-worth, dignity of labour, integrity and personal responsibility. Guidance counsellors should be employed and posted to secondary schools to help students in self-understanding and self-management as well as the development of effective study habits in relation to how they can utilize their assets and manage their abilities for optimal development.